Sebuah Studi Metode Perhitungan Fluktuasi Pemakaian Air di Apartemen Tanpa Jam Pemompaan - Laurensius Marcell; Rositayanti Hadisoebroto; Tazkiaturrizki Tazkiaturrizki (Asian Journal of Innovation and Entrepreneurship, 2022)
Apartment planning includes reservoir size planning and pumping systems for reservoirs and their distribution systems. In determining the optimal size for the reservoir, comparative data is needed from other apartments with relatively the same specifications. The data is processed to determine the maximum and minimum average water usage in a certain period of time. The optimum reservoir size can be determined based on the results of the data processing. So the method of calculating fluctuations in water use is needed to determine this, but not every apartment has the same pumping system. This research is intended for data collection in apartments that do not have definite pumping hours. The result of study shows that this method can be applied to apartments without solid timing for pumping water.